Requirements engineering process assessment and improvement approach for Malaysian software industry - Badariah Solemon, 1973-; Shamsul Sahibuddin, supervisor; Abdul Azim Abd. Ghani; Fakulti Sains Komputer dan Sistem Maklumat (2012)
Thesis (Ph.D (Sains Komputer)) - Universiti Teknologi Malaysia, 2012